Experimental Combustion : an Introduction. - Mishra, D. P. (CRC Press, 2014)
"" ... other books available in this area do not cover the detailed topics covered here. Energy and combustion is a hot issue. It is expected to be even hotter with more demand in this area as we search for cleaner methods of energy conversion from chemical to thermal energy.""--Ashwani K. Gupta, Department of Mechanical Engineering, University of Maryland, College Park, USA.